2001
DOI: 10.1007/s004420000585
|View full text |Cite
|
Sign up to set email alerts
|

An interactive effect of simultaneous death of dwarf bamboo, canopy gap, and predatory rodents on beech regeneration

Abstract: To clarify the interactive effect of the simultaneous death of dwarf bamboo (Sasa kurilensis), forest canopy gap formation, and seed predators on beech (Fagus crenata) regeneration, we analyzed beech demography from seed fall until the end of the first growing season of seedlings in an old-growth forest near Lake Towada, northern Japan. The simultaneous death of S. kurilensis took place in 1995. We established four types of sampling site differing in forest canopy conditions (closed or gap) and Sasa status (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
4
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 27 publications
4
99
4
1
Order By: Relevance
“…Researchers have also suggested that S. quelpaertensis (Kim et al 2007) and S. cernua (Li et al 1992) have allelopathic effects on their competitors. Furthermore, patches of Sasa can provide habitat for small mammals, who might consume larger seeds and indirectly prevent the regeneration of trees (Abe et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also suggested that S. quelpaertensis (Kim et al 2007) and S. cernua (Li et al 1992) have allelopathic effects on their competitors. Furthermore, patches of Sasa can provide habitat for small mammals, who might consume larger seeds and indirectly prevent the regeneration of trees (Abe et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported the disturbance of regeneration of tree species by ungulate browsing around the world (Wilson 1969, Gill 1992, Waller and Alverson 1997, Potvin et al 2003, Rooney and Waller 2003, Senn and Suter 2003, Weisberg and Bugmann 2003, Cote et al 2004, Tsujino and Yumoto 2004, Pepin et al 2006, Takatsuki 2009, Hidding et al 2012, Nagaike et al 2014Cutini et al 2015, Swiss Federal Institute for Forest 2015; a few studies were carried out on the dynamics and the other ecological issues of roe deer in Korea (Kim and Kim 2001, Kim 2006, Kim and Hong 2006, Kim et al 2007a, Jeon and Kim 2011, Jo et al 2012, 2013, Kang 2013. In addition, studies on the dynamics of forest stands indicated that competition with other species of understory vegetation such as dwarf bamboo (genus Sasa) can interrupt the establishment of the seedlings of the natural tree species at forest stands of the world (Nakashizuka 1988, Peters et al 1992, Abe et al 2001, Taylor et al 2004, 2006, Dole啪al et al 2009, Song et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Beckage et al 2000;Chac贸n and Armesto 2006;Norghauer et al 2008) or among diVerent gap sizes (Pearson et al 2003). Spatial heterogeneity in understorey cover creates a forest-Xoor mosaic of recruitment opportunities through its inXuence on abiotic conditions (George and Bazzaz 1999;Beckage et al 2000;Beckage and Clark 2003;Giordano et al 2009), litter deposition (Gray and Spies 1997;Christie and Armesto 2003), and habitat use by resident consumers (Wada 1993;Abe et al 2001;Pearson et al 2003;Caccia et al 2006;Royo and Carson 2008). Understorey vegetation may constrain tree seedling growth and survival by reducing light availability (Beckage et al 2000;Taylor et al 2004) and belowground resources (Lewis and Tanner 2000;Beckage and Clark 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Small mammals usually prefer vegetated patches, where they exert increased predation on seeds or seedlings relative to open areas (Wada 1993;Caccia and Ballar茅 1998;Abe et al 2001;Beckage and Clark 2005). Understorey patches also oVer resources to ground birds (Reid et al 2004), which may inXict physical damage on young seedlings while searching for prey (Gillman and Ogden 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation